Analysis of Teachers' Ethnolinguistic Knowledge at Primary School in Pemayung District - Medinal Ikhsan; Nur Amalina; D.M.W Munasinghe; Chimele Tina Elem (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the knowledge of class teachers about ethnolinguistics and ethnolinguistics in Elementary school at Pemayung sub-district, Pemayung, knowing strategies or knowing the strategies or ways teachers implement ethnolinguistics and the obstacles experienced by teachers in implementing ethnolinguistics in learning the Pemayung sub-district Elementary School. Methodology: This research also uses qualitative methods. This data was collected using interview techniques. Apart from that, it's high class. This data was collected using interview techniques. Apart from that, document analysis is used in the form of lesson plans which are used by teachers to complement document analysis in the form of lesson plans which are used by teachers to complete and strengthen data from questionnaires and interviews so that research results can be more and strengthen data from questionnaires and interviews so that research results can be more credible/trustworthy. Main Findings: the results obtained from the questionnaire data of 18 respondents show that for the category of high ethnolinguistic knowledge there were 4 out of 18 teachers with a percentage of 22.2%, medium 55.6% with a total of 10 out of 18 teachers, low as many as 4 out of 18 teachers with percentage 22.2%. This shows that elementary school teachers in Pemayung subdistrict have dominant ethnolinguistic knowledge in the medium category with a percentage of the medium category, by 55.6% that is as much 10 of 18 person Teacher. Novelty/Originality of this study: The research makes a new contribution to the field of education by exploring in depth teachers' understanding of the relationship between language, culture and the learning process. This research opens the door to a more comprehensive understanding of how ethnolinguistic factors influence learning approaches at the primary level, particularly in diverse cultural contexts in Pemayung Regency.